Use of Medical Applications By Students During Emergency Medical Training - Yilmaz, Mustafa; Goktekin, Mehmet Cagri (My University, 2020)
Introductıon:Thisstudyaimedtodeterminethe frequency of medical application (medical app) use in emergency medical training by 6th year (senior year) medical faculty students and the contribution of these applications to learning.Materials and Methods:The population of this study consisted of 6th year (senior year) medical students who completed their emergency medical internship training. Online questionnaires were prepared based on literature data and experience, and the students were asked to complete these questionnaires on a voluntary basis.Results:Surveys were completed by 95 students who agreed to participate, 45 of these students who did not receive Emergency Medicine internship were excluded from the study.. Of the participants, 38.6% (n = 22) were female and 61.4% (n = 35) were male, while 56.1% (n = 32) were between the ages of 18-24 and 43.9% (n = 25) were between the ages of 25-29. Of the students, 68% thought that, compared to the other branches, medical app use increased to a greater extent during emergency medical training. It was found that 70% of the students used medical apps in the emergency room to access information such as drug dosage and indications, while 62% used medical apps to learn about ECG. It was found that80%ofthestudentsneverorrarelyused applications that contained medical calculators.Conclusıon:Medical app use by senior medical faculty studentsduringtheiremergencymedicaltrainingis increasing. Students use applications on drugs, ECG and radiologicalevaluationmorefrequently,comparedto applications on medical dictionary, anatomy and medical calculators.
Keywords: Tıbbi İnformatik; Acil Tıp